Visual Pollution of Commercial Street Sidewalks: A Case Study of Design Standards in Al-Hilla City, Iraq - Hussein, Athraa Hamza; Al-Anbari, Mohammad Ali (Journal of engineering sciences and information technology, 2024)
This study investigates the impact of subpar sidewalk design standards on the aesthetic quality of commercial streets. Sidewalks, exemplified by Roman constructions, have historically played a crucial role in urban infrastructure, fostering pedestrian safety and social interaction. The research focuses on Street 40 in Al-Hilla city, examining how inadequate design standards contribute to aesthetic degradation. Previous research has addressed visual pollution in urban environments, but few have specifically examined sidewalks. This study addresses this gap by analyzing design standards in Street 40.The findings reveal that current sidewalk design falls short of required standards. Inconsistent width, variations in finishing materials, and a lack of consideration for building heights relative to sidewalk level all contribute to a diminished aesthetic experience. Moreover, the sidewalks serve functions beyond pedestrian use, accommodating advertising and merchandise display, further highlighting the need for improved design. The research concludes by proposing recommendations to enhance sidewalk aesthetics, including ensuring adequate width, maintaining design consistency, reserving sidewalks for pedestrians and designated furniture, and implementing color differentiation for improved pedestrian navigation.
Keywords: تصميم الأرصفة; الجمالية الحضرية; الشوارع التجارية; البنية التحتية للمشاة; مدينة الحلة